Efficacy and survival outcome of allogeneic stem-cell transplantation in multiple myeloma: meta-analysis in the recent 10 years - Lin, Si Yu; Lu, Ke Jie; Zheng, Xiao Na; Hou, Jian; Liu, Ting Ting (Frontiers in Oncology, 2024)
Allogeneic hematopoietic cell transplantation (alloHCT) possessed direct cytotoxicity and graft-versus-multiple myeloma effect (GvMM). Growing trials have shown survival benefits of performing alloHCT in both newly diagnosed and relapsed MM. We aimed to provide a comprehensive analysis among the recent ten years to verify the efficacy and survival outcome of alloHCT in MM patients. 61 Studies which provide data between 14 April 2013 to 14 April 2023 and a total of 15294 data from MM patients who had undergone alloSCT were included in our study. Best response rates (CR, VGPR, PR) and survival outcomes (1,2,3,5,10 year-OS, PFS, NRM) were assessed. The pooled estimate CR, VGPR and PR rate was 0.45, 0.21 and 0.24 respectively. The pooled estimate of 1, 2, 3, 5, 10-year OS was 0.69, 0.57, 0.45, 0.45, 0.36 respectively; the pooled estimate of 1, 2, 3, 5, 10-year PFS was 0.47, 0.35, 0.24, 0.25, 0.28 respectively; the pooled estimate of 1, 2, 3, 5, 10-year NRM was 0.16, 0.21, 0.16, 0.20, 0.15 respectively. Our results showed constant OS, PFS, and NRM from third year onwards till the tenth year, suggest that alloSCT has sustained survival benefits.We further conducted meta-analysis in NDMM/frontline setting and RRMM/salvage setting independently. In NDMM/upfront setting, the pooled estimate CR rate was 0.54, 5-year OS, PFS, NRM was 0.69, 0.40, 0.11 respectively. In relapsed setting, the pooled estimate CR rate was 0.31, 5-year OS, PFS, NRM was 0.24, 0.10, 0.15 respectively. Good response rate and promising survival outcome was observed in NDMM/frontline setting.Although comparing with other treatments, alloSCT had a lower response rate and poorer short-term survival outcome, long-term follow-up could reveal survival benefits of alloSCT in MM patients.